Diatom diversity during two austral summers in the Ross Sea (Antarctica) - Saggiomo M.; Escalera L.; Bolinesi F.; Rivaro P.; Saggiomo V.; Mangoni O. (Marine Micropaleontology, 2021)
Phytoplankton blooms in the Ross Sea generally occur during late spring-early summer, especially in the marginal ice zone, polynya areas and continental shelves. These blooms are generally dominated by many species of diatoms and the haptophyte Phaeocystis antarctica, and are driven by water column dynamics. However, most of the information on diatoms in the Ross Sea regards their ecological and biogeochemical role in Antarctic waters, with few and fragmented data describing the species composition. In order to contribute to the information on diatom diversity in the Ross Sea, data from two oceanographic cruises carried out in austral summers 2014 and 2017, have been analyzed also with respect to their spatial variability. Up to four genera, such as the pennates Fragilariopsis and Pseudo-nitzschia and the centrics Dactyliosolen and Chaetoceros, were mainly observed during the cruises. In both years, pennates dominated at coastal stations in early summer, while centric diatoms dominated in offshore waters particularly at 0 m in mid-summer. The most abundant species was Pseudo-nitzschia subcurvata contrarily to that reported by previous studies where Fragilariopsis curta and F. cylindrus were the most abundant species. Regarding the role of diatoms in the Antarctic food web, changes in species composition should be considered in light of recent studies on the effect of the ongoing climate change in the Ross Sea.